The Impact of Thermal History on Buildings Occupants’ Thermal Assessments in Air-Conditioned Office Buildings - Norfadzilah, Jusoh; R. A., Bakar; Ahmad Rasdan, Ismail; Tanti Zanariah, Shamshir Ali; Shamshir, Ali; Farrah Wahida, Mustafar (Academic Research Online Publisher, 2015)
he aim of this study was to investigate physiological factor that may affect worker performance in office building. Air conditioning is essential for maint aining environment thermal comfort in indoor the building, especially for climates such as Malaysia. To investigate of the thermal sensation of people located in no -uniform environment, it is very important to define the local heat transfer detail. In this context, the purpose was to make thermal comfort comparison between temperature settings of air conditioning. The temperature was maintained at five different levels which are 19, 21, 23, 26 and 29 oC. The study was carried out in environmental chamber at Univeristi Malaysia Pahang. The result shows temperature ranges between 21oC -29oC and relative humidity 50% - 60% give difference heart rate level that indicates the level of comfort by subjects